Information Integrity Violations and Intellectual Property Theft Factors for Better Controlling Plagiarism Through Technological Regulators - Rousseau, Joseph (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Information integrity and security are of the utmost importance in both an academic and a business setting. In an academic setting, the most often talked about information integrity violation is plagiarism. The current means for detecting and controlling plagiarism in a university setting relies on the use of plagiarism detection software. Though this software is able to detect certain types of plagiarism, many forms will go unnoticed. Consequently, as a sole means to police information integrity violations in the academic domain, this software is ineffective. The research here looks to provide an improved user interface design for the results of such software in the hopes that it can modify the behaviour of potential plagiarists. The goal of this research is to attack the problem of plagiarism from a different angle by focusing on modifying the behaviour of potential plagiarists rather than focus on a simple law based system. In the view of Lessig, this thesis introduces a technological regulator to plagiarism prevention. In addition, links have been made to the potential use cases of such software in a business environment for the security of enterprise information. This research has found that the introduction of a technological regulator has been helpful to change the behaviour of potential plagiarists. This research is conducted using the method of design science research.